Peritonitis in recent years: clinical findings and predictors of treatment response of 170 episodes at a single Brazilian center - Oliveira, Luiz Gustavo [UNESP]; Luengo, Juliana [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Montelli, Augusto C. [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP]; Barretti, Pasqual [UNESP] (Springer, 2012)
Peritonitis continues to be a major cause of dropout in peritoneal dialysis (PD) patients. Changes in the prevalence of peritonitis etiologies and an increase in the frequency of methicillin-resistant coagulase-negative staphylococci (CoNS) and Gram-negative species resistant to commonly used antibiotics have been reported. As a consequence, the current clinical presentation and patient outcome may differ from classical descriptions. The objectives of this study were to describe the clinical and microbiological characteristics of PD-related peritonitis episodes that occurred over a period of 6 years at a single Brazilian dialysis center and to identify predictors of outcome.A total of 170 peritonitis episodes that occurred in 92 PD patients between January 2004 and December 2009 were reviewed. Multivariate analysis was used to identify demographic, clinical, and microbiological factors predicting endpoints (resolution and peritonitis-related death). Patients' characteristics and peritonitis incidence, etiology and outcomes were compared with a series of 232 episodes that occurred in the first 6 years (1995-2000) of the PD program at the same center.The overall peritonitis rate was 0.65 episodes/patient-year. Gram-positive cocci were identified in 79 (46.5%) episodes, whereas Gram-negative bacilli were isolated from 48 (28.2%). CoNS were the main Gram-positive species identified in 48 episodes. of these, 56.3% were resistant to methicillin. Among Gram-negative species, amikacin resistance was observed in 60% of non-fermentative Gram-negative bacilli (NFGNB) and in only 3.6% of Enterobacteriaceae. The overall resolution rate was 44.1%. Oxacillin resistance and NFGNB etiology were strong predictors of non-resolution, whereas older age was the only predictor of death. Antibiotic protocols did not influence outcome. Comparison with the results obtained for the 1990-1995 period showed a lower peritonitis rate, a strong decline in the proportion of Staphylococcus aureus episodes, a significant increase in the frequency of oxacillin-resistant CoNS and amikacin-resistant NFGNB, and a significantly lower resolution and higher death rate.The current clinical characteristics and outcome suggest a greater severity of peritonitis episodes and higher risk of death, possibly due to bacterial resistance. Older age is a risk factor for death.
Keywords: Peritonitis; Peritoneal dialysis; Clinical findings; Treatment; Etiology; Outcome